A study on fire system management in shopping complexes at Johor Bahru / Siti Zaharah Barook - Barook, Siti Zaharah (Faculty Architecture, Planninng and Surveying, 2014)
Quite often if not always, it is the occupants for no mistake of their own who fall victim to fire. Besides damage to their belongings and property, some occupants are burned to death for not knowing what to do in the event of fire. Even though shopping complexes are provided with the most sophisticated fire system features, assurance of safety to building occupants is questionable and held in doubt. Fire outbreaks occur as a result of “human factors”, such as carelessness, negligence or simply a lack of fire safety awareness. In response to this, fire system management has become an integral aspect in the daily operations of shopping complexes. This study presents the results of the investigation on fire system management in shopping complexes. The objectives of the study are to study on fire system management in shopping complexes; to highlight a problem in managing fire system management; and to recommend the improvement that should be taken in improving the fire system management. The methodology for conducting the study involved literature review, data collection and analysis of results using the Average Index Method. The process of data collection involved obtaining primary data from the respondents by conducting questionnaire surveys at the selected building case studies. From this study, it is determined that the three most problem procedure in managing of fire system management are the education and training of shopping complexes occupants in fire safety; inspection of electrical installations; and to provide clear signage indicating exit routes and location of fire safety equipment. The three best improving management of fire system are to implement good and regular housekeeping procedures; to ensure that there are clear signage which is the “glow in the dark” representing exit routes and location of fire safety equipment; and install high-tech fire system equipment in shopping complexes. It is hoped that this study will provide some useful insight on the important improvement of Ffre system management and thus, help guide shopping buildings occupants to safeguard both their life and property.